Apstrakti sa stručnog skupa Filozofija u učionici - Zoran Bašić; Danijela Grujić; Iris Janković; Miloš Jeremić; Marija Jovanović; Aleksandra Maksić; Damir Malešev; Mirko Marković; Siniša Mitrić; Aleksandra Peričin (A Priori)
Apstrakti